Upaya Meningkatkan Hasil Belajar PKn Siswa Sekolah Dasar pada Materi Pokok Proses Globalisasi Melalui Model Pembelajaran Inkuiri Terbimbing - Hayati, Nur (Saneskara: Journal of Social Studies, 2024)
This study explored the application of the guided inquiry learning model to Civics learning in elementary schools. The problems of this research are 1) How good is the picture of Civics learning outcomes of grade IV students of SD Negeri 2 Usuku who are taught using guided inquiry learning techniques on the material of the globalization process? 2) How is the development of the results of Civics learning activities for grade IV students of SD Negeri 2 Usuku through applying the concept of guided inquiry learning on the subject matter of the globalization process? This research has a target to 1) be able to describe the results of Civics learning activities of grade IV students of SD Negeri 2 Usuku who are taught by applying a guided inquiry learning model; 2) describe the improvement of Civics learning activities of grade IV students of SD Negeri 2 Usuku who are taught by applying guided inquiry learning. The subjects of this learning improvement research were grade IV students of SD Negeri 2 Usuku totaling 18 students. The results of this study show that the results of Civics learning activities of grade IV students of SD Negeri 2 Usuku through the application of guided inquiry learning can be improved, the results of cycle I learning, which reached 64%, show this. Cycle II gets a completeness percentage of 76%, and cycle III shows a completeness percentage of 88%. Based on the findings of this study, teachers may consider using the guided inquiry learning paradigm as a substitute to make it easier for students who experience barriers in learning civics lessons.